Political Economy of Fiscal Reform in Central and Eastern Europe - Kopits, George (Competitio, 2009)
The reform of public finances has been at the centre of the post-socialist transition of Central and Eastern Europe since the early 1990s. At various stages of the transition, the reform process encompassed the entire gamut of public finances: the national budget, sub-national finances, extrabudgetary operations, and state-owned financial and non-financial enterprises. For the most part, fiscal reform was a non-linear stop-and-go process – often characterised by backtracking as well – and was uneven across countries. Moreover, unlike most reform experience in the rest of the world, fiscal reform in this region took place against the backdrop of a radical break, as sovereign countries emerged from a colonial past following the collapse of the Soviet Union. An important milestone was reached in 2004–2007, when all ten countries covered in this article became members of the European Union. The purpose of this article is to discuss fiscal reform in Central and Eastern Europe from the perspective of political economy. Following an overview of basic reform trends, the article focuses on the principal drivers and impediments to reform in the region. To conclude, the ingredients of successful reform are examined. The article does not provide an exhaustive inventory of reform measures, nor does it offer a survey of broad political economy issues prior to or during the transition period. Country references are intended to serve as stylised illustrations of main points, rather than as a comprehensive documentation of reform episodes.Journal of Economic Literature (JEL) classifications: H1, H3, P2, P52.